Risk Factors of Coal Worker’s Pneumoconiosis (CWP): A Systematic Review - Guspianto, Guspianto; Aswin, Budi; Dewi, Nur Juninda (Riset Informasi Kesehatan, 2024)
Background: Coal worker’s pneumoconiosis (CWP) is a parenchymal lung disease caused by inhalation of dust from coal mines. In global, the prevalence of CWP was 18.8% in 2013, while in Indonesia the data was still scarce, despite having many coal mines. This was still be most important occupational disease issue in Indonesia. This study aims to obtain an overview of the risk factors for CWP including dust, length of exposure, susceptibility, and smoke through a systematic review. Method: Search articles using four databases namely Google Scholar, Scopus, PubMed, and ScienceDirect using the PRISMA method using keywords “coal worker’s pneumoconiosis” or “black lung” and “dust” and “long exposure” and “susceptibility” and “smoking. 14 articles that met the inclusion criteria were selected from 1,195 articles in the initial. Results: A review of articles showed that the factor of dust, length of exposure, and individual susceptibility proved to be risk factors that influence and develop CWP, while smoking was not associated with the incidence of CWP, but could interfere with lung function. Conclusion: It is recommended that coal mining workers always use personal protective equipment (PPE), especially respiratory protective equipment, maintain body stamina with adequate nutritional intake and rest, regular health checks, and do not smoke.